Assessment of Entrepreneurship in Indonesia Towards Compliance on Facing Afta - Hendry Hartono; Erwin Halim (Binus Business Review, 2013)
Entrepreneurship as a process of establishment of SMEs or business ventures in many sectors, have greatly contributed in the creation of jobs, innovation and to economic growths. Economic activities of large company tend to create opportunities for SMEs through creating new market as technology implementation. Government supports are needed to provide national intermediaries for supporting the entrepreneur to start the business, also preparing them for global competitive market. Intermediaries support government for educate entrepreneur increase their skill, knowledge, and motivate them as a coach. Intermediaries can from expert individual, private institution, and higher education institution. The purposes of this paper are to assess entrepreneurship in Indonesia and to offer some recommendations that can be followed up that can significantlygive positive impact on entrepreneurship development in Indonesia ahead of the implementation of AFTA.